Ice Camp (PRELIMINARY) CTD Yoyo Cast Analysis Time (ASCII) (PSC). Version 1.0 [PRELIMINARY] ... - Morison, J.; McPhee, M.; Stanton, T.; Martinson, D.; University Of Washington (UCAR/NCAR - Earth Observing Laboratory, 2007)
This data set contains data from a PRELIMINARY analysis of every 10th downcast of the yoyo Conductivity Temperature Depth (CTD) between the start of SHEBA and the end of January 1998. It is made from Tim Stanton's field summary data analysis. These are the data that were shown in contour form at the March 1998 meeting. This particular data set contains data on time, giving the time of each of the 192 sample profiles in SHEBA days. See also the companion data sets containing Depth (13.726), Temperature (13.728), Salinity (13.729), and Density (13.730). ...